1999
DOI: 10.1023/a:1021858012332
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Understanding the consequences of maltreatment, including poor academic performance and adaptive functioning, is important in planning educational, health, and social service interventions that may help abused or neglected children succeed in school and later in life. Longitudinal analysis is the best way to establish a causal relationship between maltreatment and subsequent school problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Mothers, as compared to fathers, reported higher rates and more frequent use of corporal punishment on their children. 42 it could be because of high stress of mothers in daily life. In the middle class families in Tripura, the majority of the mothers are working outside for earning money to run the family comfortably after doing all household chores and looking after the children.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers, as compared to fathers, reported higher rates and more frequent use of corporal punishment on their children. 42 it could be because of high stress of mothers in daily life. In the middle class families in Tripura, the majority of the mothers are working outside for earning money to run the family comfortably after doing all household chores and looking after the children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Eckenrode, Laird, and Doris (1993) found that maltreated children had lower test scores in math and reading, lower grades, increased levels of grade repetition, and more disciplinary referrals than their non-maltreated counterparts. Zolotor and colleagues (1999) found that substantiation of child maltreatment was significantly predictive of poor school performance within their high-risk sample. Further, Leiter and Johnsen (1994) found that maltreated children fared significantly worse than comparison children on a range of school-related outcomes, including standardized test scores, GPA, and grade retention.…”
Section: Introductionmentioning
confidence: 94%
“…Les nombreuses recherches étudiant spécifiquement le lien entre la maltraitance et le développement cognitif convergent toutes vers la même conclusion : l’enfant subissant de la maltraitance aura tendance à vivre plus de difficultés à l’école que celui n’en subissant pas (Eckenrode, Laird & Doris, 1993; Leiter & Johnsen, 1994; Rowe & Eckenrode, 1999; Stone, 2007) et celles-ci persistent jusqu’à l’âge adulte (Perez & Widom, 1994). Des études au devis longitudinal ont démontré que la présence de maltraitance permettait de prédire un déclin sur le plan de la réussite scolaire (Coohey, Renner, Hua, Zhang & Whitney, 2011; Fantuzzo, Perlman & Dobbins, 2011; Leiter & Johnsen, 1997; Zolotor et al, 1999), qui s’expliquerait par l’entremise de déficits sur le développement cognitif et intellectuel (Irigaray et al, 2013; Veltman & Browne, 2001). La maltraitance parentale peut prendre plusieurs formes, notamment la négligence physique, la négligence émotionnelle ou l’abus physique, sexuel ou psychologique.…”
unclassified